METHODS FOR ASSESSING MANAGEMENT EFFICIENCY IN INDUSTRIAL ENTERPRISES - Mamanazarov Oybek Shomurodovich (Modern American Journals, 2025)
The article provides a theoretical and practical analysis of employee performance evaluation based on the system of key performance indicators (KPIs) at industrial enterprises of Kashkadarya region, material and non-material incentives affecting the system of employee performance evaluation, training and, based on the results of a social survey, analyzed the professional development of employees, organized labor management system and employee dissatisfaction, considered as the final the result for them, according to the results of the social survey, relevant conclusions and proposals have been developed.
Keywords: Key performance indicators (KPI) system, performance of work, training and development of employees, organization of work, motivation of employees, employee dissatisfaction.